2016
DOI: 10.1007/s00604-016-2029-7
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanoparticle modified screen printed carbon electrode as a disposable electrochemical immunosensor strip for the detection of Japanese encephalitis virus

Abstract: The authors describe a disposable electrochemical immunosensor strip for the detection of the Japanese encephalitis virus (JEV). The assay is based on the use of a screen printed carbon electrode (SPCE) modified with carbon nanoparticles (CNPs) that were prepared from starch nanoparticles and deposited on the SPCE working electrode whose surface was functionalized with 3-aminopropyl triethoxysilane. Next, antibody of JEV was immobilized on the surfaces of the CNPs. The analytical performance of immunosensor st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…3a) (De Luna et al 2017;Mahshid et al 2016). A study by Chin et al found that nanostructuring of carbon electrodes with carbon nanoparticles enhanced the electron transfer kinetics and current intensity of the electrode by 63% for the detection of Japanese encephalitis virus (Chin et al 2017).…”
Section: Electrode Nanostructuringmentioning
confidence: 99%
“…3a) (De Luna et al 2017;Mahshid et al 2016). A study by Chin et al found that nanostructuring of carbon electrodes with carbon nanoparticles enhanced the electron transfer kinetics and current intensity of the electrode by 63% for the detection of Japanese encephalitis virus (Chin et al 2017).…”
Section: Electrode Nanostructuringmentioning
confidence: 99%
“…The functionality of the electrochemical biosensor can be further improved by nanostructuring the electrode as it increases the electrochemical reaction rate due to an increased electrode surface area to volume ratio, thereby increasing the electrode surface area to analyte fluid volume. In the work by Chin et al on the encephalitis virus, it was found that nanostructuring of carbon electrodes with carbon nanoparticles increased the current response by 63% due to an enhanced electron charge transfer kinetics [ 23 ]. Similarly, we have reported that Co functionalized TiO 2 nanotubes (Ni-TNTs) with higher surface-to-volume ratio can detect the biomarkers associated with tuberculosis [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The functionality of the electrochemical biosensor can be further improved by nanostructuring the electrode as it increases the electrochemical reaction rate due to an increased electrode surface area to volume ratio, thereby increasing the electrode surface area to analyte fluid volume. In the work by Chin et al on the encephalitis virus, it was found that nanostructuring of carbon electrodes with carbon nanoparticles increased the current response by 63% due to an enhanced electron charge transfer kinetics [23]. Similarly, we have reported that Co functionalized TiO2 nanotubes (Ni-TNTs) with higher surface-to-volume ratio can detect the biomarkers associated with tuberculosis [24] [25].…”
Section: Introductionmentioning
confidence: 81%